Solution-processed ZnO coated on LiNi0.8Mn0.1Co0.1O2(NMC811) for enhanced performance of Li-ion battery cathode - Kang, Chiwon; Park, Yewon; Kim, Yongjoon; Kim, Soo Min; Ha, Seungho; Yoon, Hee Gon; Oh, Kyu Won; Shin, Keun-Young; Kim, Byung Hyo (Frontiers in Energy Research, 2023)
The LiNi0.8Mn0.1Co0.1O2 (NMC811) cathode material, widely used in Li-ion batteries(LIBs) for electric vehicles (EVs), has gained a fair amount of attention in the industry due to its advantages of high energy capacity and low production cost. However, during charge-discharge cycles, NMC811 cathode faces issues such as hydrofluoric acid (HF) attack, leaching of transition metals and unstable formation of the cathode-electrolyte interphase (CEI), which leads to undermining cathode performance. To address these issues, extensive research has been conducted on coating materials based on metal oxides. In this study, our research team chose Li-doped ZnO (LZO) material, known for its high Li + ion conductivity and structural stability. Employing sol-gel synthetic method, we successfully coated LZO material on commercial NMC811 particles, therefore ensuring its coating uniformity through X-ray photoelectron spectroscopy (XPS) and energy-dispersive X-ray spectroscopy (EDS) analyses. Evaluation of the coated samples (1 wt%, 2 wt%, and 3 wt% LZO on NMC811) revealed their superior electrochemical performance compared to bare NMC811; furthermore, the 2 wt% LZO-coated sample exhibited the highest cycling performance among the coated samples. These findings could be attributed to the lower charge transfer resistance verified by electrochemical impedance spectroscopy (EIS) analysis. Thus, we confirmed the LZO coating layers could provide stability for the NMC811 surface structure, mitigate the leaching of transition metal ions in the NMC811, and promote the formation of an enhanced CEI layer, therefore facilitating Li + ion diffusion.